2020
DOI: 10.1111/1440-1703.12124
|View full text |Cite
|
Sign up to set email alerts
|

Phenology in a community context: Toward a better understanding of the causes and consequences of phenology in seasonal environments

Abstract: Many natural ecosystems occur in the seasonal environments, where phenological species interactions are the hallmark of community dynamics and biodiversity effects on ecosystem functions may be realized through phenological diversity. To understand and forecast the impacts of global climate change, phenologically explicit community dynamics should provide a useful perspective. We hope that this special feature will serve as pointers for future research on phenological interactions in multispecies ecological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Our results contribute to growing evidence that phenological diversity, not simply abundance, is an important component of energy flow within upper trophic levels of food webs in seasonally dynamic ecosystems (Armstrong et al, 2016;Takimoto and Sato, 2020). For instance, we observed that the magnitude of the bird response was not associated with total salmonfly C flux, nor with the total number of adult salmonflies present in the reach, but was instead apparently more closely linked to timing of prey occurrence.…”
Section: Discussionsupporting
confidence: 65%
“…Our results contribute to growing evidence that phenological diversity, not simply abundance, is an important component of energy flow within upper trophic levels of food webs in seasonally dynamic ecosystems (Armstrong et al, 2016;Takimoto and Sato, 2020). For instance, we observed that the magnitude of the bird response was not associated with total salmonfly C flux, nor with the total number of adult salmonflies present in the reach, but was instead apparently more closely linked to timing of prey occurrence.…”
Section: Discussionsupporting
confidence: 65%
“…In comparison, we still know surprisingly little about how communities are organized in time, which has only recently gained renewed attention as a line of research (Post 2019;Wolkovich et al 2014;Yang 2020). The ongoing and projected impacts of climate change on ecological communities, as well as calls for their short-and long-term mitigation and adaptation plans (IPCC 2023), create an urgency to develop frameworks explicitly focusing on the temporal dimension of community structure to fill this conceptual gap (CaraDonna et al 2021;Rudolf 2019;Takimoto & Sato 2020;Wolkovich et al 2014;Yang 2020;Yang & Rudolf 2010).…”
Section: The Temporal Dimension Of Community Structurementioning
confidence: 99%
“…The ongoing and projected impacts of climate change on ecological communities, as well as calls for their short- and long-term mitigation and adaptation plans (IPCC 2023), create an urgency to develop frameworks explicitly focusing on the temporal dimension of community structure to fill this conceptual gap (CaraDonna et al . 2021; Rudolf 2019; Takimoto & Sato 2020; Wolkovich et al . 2014; Yang 2020; Yang & Rudolf 2010).…”
Section: The Temporal Dimension Of Community Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, phenological synchrony or asynchrony with other organisms can critically affect individual fitness and population dynamics (Brommer et al 2002, Durant et al 2005, McNamara et al 2011). The view of interaction asynchrony is particularly important today owing to the impact of climate change on biodiversity (Visser and Both 2005, Yang and Rudolf 2010, Nakazawa and Doi 2012, Takimoto and Sato 2020). Climate change has species‐specific effects on the timing of seasonal life‐history events, such as reproduction and migration (so‐called phenological shifts), thereby influencing the strength of biotic interactions and altering ecological communities in a more complex way than previously thought (Thackeray et al 2010, 2016, Hällfors et al 2020, Wolkovich and Donahue 2021).…”
Section: Introductionmentioning
confidence: 99%